A novel horizontal universal viscous damping amplification device and seismic response analysis - Bao, Chao; Han, Mengfan; Bai, Pengcheng; Fan, Qi; Wang, Weiqiang; Ma, Xiaotong; Lv, Jianning; Lim, Kar Sing (Elsevier Ltd, 2025)
The application of damping amplification technology to dampers can effectively enhance the energy dissipation efficiency and address the issue of underutilization during small displacements. In this study, a novel horizontal universal damping amplification device (HUDAD) is proposed, and its construction and operational mechanism are detailed. A restoring-force model for the horizontal universal viscous damping amplification device (HUDAD-VD) is derived, which integrates viscous dampers, establishing its equations of motion and energy balance. Furthermore, pseudo-static tests are conducted to validate the damping amplification and energy dissipation capabilities of the HUDAD-VD. Finally, a seismic response analysis of a multi-degree-of-freedom damping system incorporating the HUDAD-VD is performed to evaluate its seismic performance. The results show the close alignment between the experimental and theoretical hysteretic curves of the HUDAD-VD, confirming the accuracy of the theoretical model. The HUDAD-VD demonstrates effective damping performance under all levels of seismic action, successfully controlling the displacement within the seismic isolation layer. In particular, the HUDAD exhibits a satisfactory amplification effect, effectively enhancing the damper energy dissipation.